The regulatory role of immune microenvironment-related cells and pathways in the pathogenesis of keloids - Dong, Xuan; Gao, Mingnan; Guo, Han; Wang, Peng; Zhang, Yixuan; Shang, Qiaoli; Wang, Qiying (Frontiers in Immunology, 2025)
Keloids are skin lesions caused by excessive fibrotic reactions, and their pathogenesis is not yet fully understood. Recent studies have shown that the immune microenvironment plays a significant role in the development of keloids. This article reviews the distribution and functions of immune microenvironment-related cells in keloids, including keratinocytes, fibroblasts, mast cells, macrophages, T cells, and stem cells, as well as the interactions between these cells and local cells. The article also explores the impact of several signaling pathways within the immune microenvironment on keloid formation, including the transforming growth factor β pathway (TGF-β), PI3K/Akt/mTOR signaling pathway, Wnt/β-catenin signaling pathway, and Notch signaling pathway. These pathways recruit more immune cells by secreting various cytokines and inflammatory mediators, stimulate fibroblast proliferation and collagen synthesis, ultimately leading to the formation of keloids. By deeply analyzing the roles of cells and their signaling pathways within the immune microenvironment, we can provide potential new targets for the treatment of keloids.